Clinical Significance of Thymomegaly in Children with Congenital Heart Defects - G.G. Makhkamova (Zien Journals, 2026)
Children with thymomegaly exhibit impaired adaptive capacity associated with functional changes in the hypothalamic–pituitary–adrenal system, while their immunological insufficiency contributes to the development of infectious complications. They represent a group with reduced biological system reliability; therefore, assessment of thymic status is essential for improving outcomes of surgical correction of congenital heart defects in children.
Keywords: children; congenital; reduced biological system; development